Pandas for beginners : a quick guide. (Packt Publishing, 2022)
If you work in any functional areas of data analysis, machine learning, and artificial intelligence, you will want to be familiar with or master Pandas. Pandas is a popular Python library used for data analysis and manipulation, commonly used with data analysis, artificial intelligence, and machine learning. Pandas enables quick and efficient data manipulation, aggregation, pivoting, and flexible time series. This course will introduce you to the basics of data analysis using the Pandas library. You will learn to work with two primary data structures in Pandas, Series and Data Frame. Then, we will take a look at how to read data from a file and explore input data using indexing and filtering, at which point you will be ready for data preprocessing. Next, we will focus on handling missing values and duplicate rows and transforming data into a more efficient format. You will also discover how to manipulate data and data processing. Finally, we will dive into creating simple plots to visualize the data. By the end of this course, you can use OOPs paradigm to create class hierarchies with the OOP design process. You can design and implement Python programs for complex issues and make good use of the features like classes and inheritance. What You Will Learn Learn basic data analysis with Pandas' open-source Python library Use the two primary Pandas data structures, Series and DataFrame Process varied data types and manipulate data with string function Organize input with index and filter, preprocess data with Pandas Format and process different kinds of data most efficiently Manipulate, aggregate, and pivot data flexibly and efficiently Audience This course targets beginner Python developers or those who want to learn and use the Pandas library for Python. Data analysts, project management analysts, and those working in artificial intelligence, machine learning, or data science can benefit from this course immensely. For those managers and executives that handle a lot of data and create analytic reporting material, this course could help them as well in their data science projects. This course assumes no previous experience in Pandas, but a fundamental understanding of basic Python syntax is needed since it is built for Python. About the Author Simon Sez IT: Simon Sez IT has offered technical courses since 2008 for individuals, small businesses, and Fortune 500 companies with thousands of employees who can benefit from the easy-to-learn and hands-on software training. It offers over 8000 video tutorials on a range of software programs. Simon Sez IT ensures stress-free eLearning and enhanced employee productivity--whether you implement new software or a technological upgrade in your work environment. With over 600,000 students from 180 countries, Simon Sez IT is the preferred online learning choice for individuals and businesses worldwide.